PENGARUH KEBIJAKAN DIVIDEN, MEKANISME GOOD CORPORATE GOVERNANCE, DAN KUALITAS AUDIT TERHADAP AGENCY COST - Indra Kencana Mukti, (2021)
This research aims to determine the effect of dividend policy, implementing good corporate governance mechanism and audit quality on agency cost of listed manufacturing companies in Indonesia Stock Exchange in the period 2017 - 2020. The type of this research is quantitative research that uses secondary data based on annual report. A sample of this research consisted of 132 manufacturing companies. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linear regression, f test and partial hypothesis testing (t test). Based on the result of data analysis, it can be concluded that (1) dividend policy has no effect on agency cost, (2) audit commitee has no effect on agency cost, (3) institutional ownership has no effect on agency cost, (4) independent board commissioners has a negative significant effect on agency cost, and (5) audit quality has no effect on agency cost,